2021
DOI: 10.1111/andr.13075
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation and sperm donation in transgender individuals: The current situation within the French CECOS network

Abstract: Bérengère Ducrocq and Nathalie Rives both contributed as last co-authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
2
0
4
Order By: Relevance
“…The report of the Biomedicine Agency on FP activity showed that 90% of MFP procedures with medical indication (cancer or other) are performed in the CECOS network centres. This result confirms the data assessed by a previous national study [ 31 ] and shows that the patient’s pathway for MFP before cancer treatment in France is mainly oriented towards CECOS network centres.…”
Section: Discussionsupporting
confidence: 91%
“…The report of the Biomedicine Agency on FP activity showed that 90% of MFP procedures with medical indication (cancer or other) are performed in the CECOS network centres. This result confirms the data assessed by a previous national study [ 31 ] and shows that the patient’s pathway for MFP before cancer treatment in France is mainly oriented towards CECOS network centres.…”
Section: Discussionsupporting
confidence: 91%
“…La loi de Bioéthique du 02/08/2021 précise explicitement que « La modification de la mention du sexe à l'état civil ne fait pas obstacle à l'application du présent article [L.2141-11] ». Les centres autorisés pour la préservation de la fertilité proposent la préservation de fertilité aux personnes Trans [15].…”
Section: La Préservation De Fertilité Chez Les Personnes Transunclassified
“…Chez la femme Trans pubère, la relative facilité d'obtention des spermatozoïdes par masturbation permet de proposer facilement une congélation de spermatozoïdes éjaculés. La technique de congélation est efficace [15]. La qualité initiale du recueil de sperme ainsi que la survie des spermatozoïdes à la décongélation conditionnent la technique d'AMP réalisable avec ces spermatozoïdes congelés.…”
Section: B : Recommandations Pour Les Personnes Trans Assignées « Hom...unclassified
“…15 They found that levels of inhibin B, but not anti-Mullerian hormone, that transgender women were more likely to desire and achieve fertility preservation than transgender men. 16 Bonan et al describe the characteristics and intentions of couples involving a transgender man and cisgender female partner. 17 Finally, Aldridge et al conducted a prospective study over 18 months to assess the role of gender-affirming hormone therapy on depression and anxiety symptoms.…”
Section: Yuan Et Al Describe How Burdensome Insurance Company Require...mentioning
confidence: 99%
“…Eustache et al. found that transgender women were more likely to desire and achieve fertility preservation than transgender men 16 . Bonan et al.…”
mentioning
confidence: 99%